2017
DOI: 10.11591/ijere.v6i3.6565
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ability Grouping in Reciprocal Teaching Technique of Collaborative Learning on Individual Achievements and Social Skills

Abstract: This research focus on effects of ability grouping in reciprocal teaching technique of collaborative learning on individual achievements dan social skills. The results research showed that (1) there are differences in individual achievement significantly between high group of homogeneous, middle group of homogeneous, low group of homogeneous, and heterogeneous group in reciprocal teaching technique of collaborative learning, (2) there are differences in students social skills significantly between high group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 5 publications
0
4
0
1
Order By: Relevance
“…Penaskovic (1997) argued that such mixed groups will enhance the learning process. Another study also reported that heterogeneous grouping allows the contribution of upper ability students to lower ability students (Sumadi, Degeng, Sulton, & Waras, 2017).…”
Section: Methodsmentioning
confidence: 94%
“…Penaskovic (1997) argued that such mixed groups will enhance the learning process. Another study also reported that heterogeneous grouping allows the contribution of upper ability students to lower ability students (Sumadi, Degeng, Sulton, & Waras, 2017).…”
Section: Methodsmentioning
confidence: 94%
“…PBL research can demand students accustomed to solving problems (Dewi et al, 2023). Through collaborative learning, students will become active so that their abilities and skills can increase (Sumadi et al, 2017). This is because collaboration can help solve problems better (Yanti et al, 2023).…”
Section: Pre-revision Post-revision Figure 1 Product Revisionmentioning
confidence: 99%
“…Media inovatif yang cocok dikembangkan untuk mengatasi masalah yang ditemukan dalam proses observasi dan wawancara adalah media e-mading. Mading merupakan sebuah majalah dinding biasa dalam bentuk papan yang mana belum ada pemanfaatan teknologi di dalamnya (Komalasari & Solikin, 2018;Sumadi et al, 2017). Mading merupakan media yang berfungsi sebagai tempat berbagai informasi mengenai ilmu pengetahuan yang bervariasi dengan prinsip penyajian materi berupa tulisan, gambar, ataupun adanya kombinasi antara keduanya (Rizkalfin.…”
Section: Pendahuluanunclassified